Combustion interactions of blended coals in an O2/CO2 mixture in a drop-tube furnace: Experimental investigation and numerical simulation. (25th December 2018) - Ma, Lun; Guo, Anlong; Fang, Qingyan; Wang, Tingxu; Zhang, Cheng; Chen, Gang
Highlights: Weaker promotion and stronger inhibition are shown in O2 /CO2 than in O2 /N2 . Increasing O2 increases promotion but weakens inhibition. Promotion and inhibition in 30–35% O2 achieve similar levels to that in air. Char-CO2 reaction slightly affects promotion but greatly weakens inhibition. Increasing the reactor wall temperature weakens promotion and inhibition. Abstract: Interactions, known as the ignition promotion and burnout inhibition, exist during the combustion of blended coals in the air. The oxy-fuel conditions influence these interactions due to the change of the gas physical properties and the gasification reaction. However, little research has focused on the oxy-fuel combustion interactions of blended coals. To investigate the combustion interactions of blended coals in an O2 /CO2 atmosphere, experimental and numerical studies of the mixed combustion of less- and more-volatile coals are performed in a drop tube furnace. The results show that the more-volatile coal combustion brings the promotive effect on the devolatilization of the less-volatile coal and the inhibitive effect on the char combustion of the less-volatile coal. Compared with that in the air, the promotive effect is weaker, but the inhibitive effect is stronger in the 21%O2 /79%CO2 environment due to the different physical properties of the gases. In the O2 /CO2, increasing the oxygen concentration increases the promotive effect but weakens the inhibitive effect owing to the change of the physical properties of gases and the reactivity improvement of the less-volatile coal char. In addition, the promotive and inhibitive effects achieve a level similar to that in the air when the oxygen concentration is increased to approximately 30–35%. Furthermore, the char-CO2 gasification reaction in the O2 /CO2 has little impact on the promotive effect but weakens the inhibitive effect. Increasing the reactor wall temperature weakens both the promotive effect and the inhibitive effect.